Examining the impact of gender discriminatory practices on women's development and progression at work - Gaelle Fitong Ketchiwou; Lineo Winifred Dzansi (Businesses, 2023)
Although there has been a worldwide cry for gender equity within organizations, gender discriminatory practices continue to be a challenge. Many women still suffer from gender discrimination and remain at the bottom of organizational structures despite their efforts to ascend. This paper seeks to examine the link between gender discriminatory practices and women's skill development and progression within the workplace. The study espoused a quantitative approach. A questionnaire survey was self-administered online to 412 women through a convenient non-probability sampling method. Descriptive tendencies, test normality, validity, reliability, and regression analysis were performed using the statistical package for the social sciences (SPSS), AMOS 27. The results reveal that women's skill development is impacted by workplace gender discriminatory practices, and the career progression of women is linked to their skill development. Yet it rejects the claim that workplace gender discriminatory practices impact women's career progression. While having a gender-friendly work environment is applaudable, developing women's skills and promoting their advancement at work will require more effort from companies. Organizations need to be deliberate about the skills development and career progression of women and institutionalize initiatives that directly encourage women to engage in developmental activities as well as initiatives geared towards promoting women's career advancement.
https://doi.org/10.3390/businesses4010008
Keywords: 650; career progression; feminism; gender discriminatory practices; skills development; women; workplace